The influence of Pleistocene glaciations on Chacoan fauna: Genetic structure and historical demography of an endemic frog of the South American Gran Chaco - Brusquetti, Francisco; Netto, Flavia; Baldo, Diego; Haddad, Célio F.B. [UNESP] (Oxford University Press (OUP), 2019)
The Chaco is a semi-arid biome that has been influenced by Miocene marine introgressions and relatively recent glaciations. Marine introgressions have been suggested as an important driver of biodiversity for some Chacoan frog species, but the effects of Pleistocene glaciations have not previously been assessed. We used mitochondrial and nuclear markers to estimate the genetic structure and demographic history of Leptodactylus bufonius, a frog species widely distributed in the Chaco, to test if Pleistocene glaciations have had any influence on its evolutionary history. We found evidence to support recent range and demographic expansions and current gene flow among populations. Expansions may have occurred after the most extensive glaciations (Greatest Patagonian Glaciation and the coldest Pleistocene glaciation, 1-0.7 Mya) of the Late Pleistocene. Current gene flow is maintained by short-distance dispersal that follows a stepping-stone model allowing high connectivity, even among distant populations. Nevertheless, we cannot exclude some influence of large population sizes and retention of ancestral polymorphism in explaining the lack of population structure that we found. The genetic pattern of L. bufonius is concordant with the diversification of frogs in other semi-arid regions of the world.
Keywords: Anura; Leptodactylidae; Leptodactylus bufonius; natural history; phylogeography; semi-arid biome